2008
DOI: 10.5194/acp-8-6325-2008
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerosol organics on cloud condensation nucleus (CCN) concentration and first indirect aerosol effect

Abstract: Abstract. Aerosol microphysics, chemical composition, and CCN properties were measured on the Department of Energy Gulfstream-1 aircraft during the Marine Stratus/Stratocumulus Experiment (MASE) conducted over the coastal waters between Point Reyes National Seashore and Monterey Bay, California, in July 2005. Aerosols measured during MASE included free tropospheric aerosols, marine boundary layer aerosols, and aerosols with high organic concentration within a thin layer above the cloud. Closure analysis was ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
114
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(130 citation statements)
references
References 50 publications
16
114
0
Order By: Relevance
“…In both cases, the resulting κ for the entire aerosol is consistently lower than the 0.22 found for the OOA components in this study, where the m/z 44 to total organic fraction was 0.10 to 0.19. Other studies that have attempted to quantify κ org in the field found that using a value of 0.1 can adequately describe the CCN-activity of the aerosol at cloud-level (Wang et al, 2008) and in the Amazon rainforest (Gunthe et al, 2009). This is comparable to the campaign-wide average for this study of 0.15 for κ org , calculated using both Eqs.…”
Section: Comparison With Literature Valuessupporting
confidence: 75%
See 2 more Smart Citations
“…In both cases, the resulting κ for the entire aerosol is consistently lower than the 0.22 found for the OOA components in this study, where the m/z 44 to total organic fraction was 0.10 to 0.19. Other studies that have attempted to quantify κ org in the field found that using a value of 0.1 can adequately describe the CCN-activity of the aerosol at cloud-level (Wang et al, 2008) and in the Amazon rainforest (Gunthe et al, 2009). This is comparable to the campaign-wide average for this study of 0.15 for κ org , calculated using both Eqs.…”
Section: Comparison With Literature Valuessupporting
confidence: 75%
“…2). While the slope from the linear regression is comparable to other field studies (Broekhuizen et al, 2006;Chang et al, 2007;Medina et al, 2007;Wang et al, 2008) which have found similar values, it is calculated in a different way and puts more emphasis on the data points at high concentrations. In an attempt to lessen this effect, a linear regression of the logarithm of the concentrations was also attempted, although this resulted in a similar slope of 1.02.…”
Section: Calculations Using Oxygenated and Unoxygenated Factorssupporting
confidence: 57%
See 1 more Smart Citation
“…We assign the following individual hygroscopicity parameters: sulphate (0.61, assuming ammonium sulphate), sea salt (1.28), black carbon (0.0), and particulate organic matter (0.1). Whilst there is uncertainty associated with the hygroscopicity parameter for organic material in the atmosphere due to the wide range of solubilities observed, κ values close to 0.1 have been reported for secondary organic components (Engelhart et al, 2008(Engelhart et al, , 2011Gunthe et al, 2009;Dusek et al, 2010;King et al, 2010), and the entire organic fraction (Wang et al, 2008;Chang et al, 2010). We calculate CCN concentrations at a supersaturation of 0.2 %, which is equivalent to an activation dry diameter of approximately 80 nm (assuming a composition of pure ammonium sulphate).…”
Section: Calculation Of Ccn Concentrationsmentioning
confidence: 99%
“…However, atmospheric aerosols consist of a large number of organic compounds, which often dominate the total fine aerosol mass, especially in forested areas (e.g., de Sá et al, 2017a;Zhang et al, 2007). The hygroscopicity of aerosol organics (κ org ) have been examined in both laboratory (e.g., Asa-Awuku et al, 2009;Duplissy et al, 2011;King et al, 2009;Lambe et al, 2011;Massoli et al, 2010;Raymond and Pandis, 2003) and field studies (e.g., Cerully et al, 2015;Chang et al, 2010;Dusek et al, 2010;Gunthe et al, 2009;Lathem et al, 2013;Mei et al, 2013a, b;Moore et al, 2011Moore et al, , 2012Pöhlker et al, 2016;Rose et al, 2010;Shantz et al, 2008;Wang et al, 2008). Overall, these studies show that aerosol organics exhibit a wide range of κ values from 0 to ∼ 0.3, and κ org often increases substantially during aerosol aging in the atmosphere (e.g., Duplissy et al, 2011;Lambe et al, 2011;Massoli et al, 2010;Mei et al, 2013a, b).…”
Section: Introductionmentioning
confidence: 99%